Analysis of the Role of PPKn Teachers in Shaping the Character of Students at SMAN 11 Medan - Thaha Mulia Lubis; Abdul Marif Rambe (CV. Rayyan Dwi Bharata, 2023)
This study aims to analyze the role of PPKn teachers in shaping the character of students at SMAN 11 Medan. This study used a qualitative approach with descriptive data analysis. The source of data in this study was obtained from direct interviews with PPKn teachers at SMAN 11 Medan. The data collection of this study used interviews, observations and documenting methods. The data analysis technique used is grouping data, identifying, describing, and analyzing one by one to get the desired results and can draw conclusions from the data. The results showed that PPKn teachers at SMAN 11 Medan played a role in shaping the character of students